Nucleoprotein filament formation is the structural basis for bacterial protein H-NS gene silencing - Lim, Ci Ji (Nature Publishing Group, 2012)
H-NS is an abundant nucleoid-associated protein in bacteria that globally silences genes, including horizontally-acquired genes related to pathogenesis. Although it has been shown that H-NS has multiple modes of DNA-binding, which mode is employed in gene silencing is still unclear. Here, we report that in H-NS mutants that are unable to silence genes, are unable to form a rigid H-NS nucleoprotein filament. These results indicate that the H-NS nucleoprotein filament is crucial for its gene silencing function, and serves as the fundamental structural basis for gene silencing by H-NS and likely other H-NS-like bacterial proteins.